The engagement : a quarter century of defending, defining, and expanding marriage in America - Issenberg, Sasha (New York : Pantheon Books, 2020)
"On June 26, 2015, the United States Supreme Court ruled that state bans on gay marriage were unconstitutional, making same-sex unions legal throughout the United States. But the road to victory was much longer than many know. In this seminal work, Sasha Issenberg takes us back to Hawaii in the 1990s, when that state's supreme court first started grappling with the issue, and traces the fight for marriage equality from the enactment of the Defense of Marriage Act in 1996 to the Goodridge decision that made Massachusetts the first state to legalize same-sex marriage, and finally to the seminal Supreme Court decisions of Windsor and Obergefell. This meticulously reported work sheds new light on every aspect of this fraught history and brings to life the perspectives of those who fought courageously for the right to marry as well as those who fervently believed that same-sex marriage would destroy the nation. It is sure to become the definitive book on one of the most important civil rights fights of our time"--
Introduction : A President Decides -- The Love That Ate an Island (1990-1996) -- Inventing A Constitutional Crisis (1996) -- Inside Games (1996) -- The Second Front (1997-2003) -- "Our Team Is Not Winning" (2003-2004) -- Twenty Ten Ten Ten (2003-2007) -- The Right's Last Stand (2007-2008) -- The Road From Jersey City (2009-2012) -- Endgame (2009-2015) -- Conclusion: Back to Hawaii -- Postscript.: Massive Desistance.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Same-sex marriage -- Law and legislation -- United States -- History